CREEPING OCCUPATION COMPARATIVE STUDY AND ITS INFLUENCE ON POPULATION MIGRATION IN BORDER VILLAGES - Nino Mindiashvili; Arina Tavakarashvili (World Science, 2019)
The research covers the situation in seven villages (Gugutiaantkari, Ditsi, Kere, Ergneti, Zargiaantkari, Karapila, Dirbi) which have suffered from the creeping occupation. The research was conducted by means of the preliminarily prepared questionnaire, using the qualitative method. The research contains statistical data, with its following analysis. Based on local population we have collected materials on their social and economic situation and security issues; based on the aforementioned materials we have outlined the reasons of the flow of population from those villages. The article shows all the social and economic problems existing in listed villages and the attitude of population towards international organizations and Russia. The survey showed us different problems in each of the villages, steps towards solving of which will become the means of stopping migration from those villages. The research also reflects different opinions by experts on the ongoing processes.